Iot based real time trafic control using cloud computing - Vardhana, M.; Arunkumar, N.; Abdulhay, Enas; Vishnuprasad, P. V. (Cluster computing, 2019)
The rapid increase in the number of vehicles has given rise to the traffic jam, which is a major problem these days. The effect of traffic jam also effects the operation of ambulance. To avoid the traffic jam for the ambulance, a new idea is developed. In this paper we propose a new concept to avoid traffic jam for the ambulance and thus saving the life of an individual. At first the ambulance is detected and the information about the arrival of the ambulance is sent to the next station. The ambulance will make siren only when it carries patient inside, so by detecting both the ambulance siren and the image taken from the acquisition device, the information is sent to the next point which is on the way to hospital. Announcement of the arrival of the ambulance is done. The CCTV camera is monitoring each vehicle on that road. If any vehicle doesn’t abide by the announcement done, the image of the vehicle will be captured, and then by using the acquired image the number plate will be tracked and will be detected automatically by image processing. The vehicle information is sent to the police station, to take the necessary action. Thus the traffic control can be done and the way is cleared for the ambulance and life is saved. The processing is done using MATLAB and is verified.